2012
DOI: 10.1097/ccm.0b013e31822e9fab
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and central vascular functional alterations in the acute phase of aneurysmal subarachnoid hemorrhage*

Abstract: Our findings suggest that significant cardiovascular alterations in left ventricular function and in aortic stiffness occur during the early phase of aneurysmal subarachnoid hemorrhage. These phenomena were associated with adverse outcomes in this study and their role in the pathogenesis of delayed neurologic complications warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…Although similar results were previously described [9], others studies showed LV systolic dysfunction in 22 to 38% acute phase SAH patients [6,40]. This fact probably resulted from our exclusion criteria of patients with a major hemodynamic instability preventing intrahospital transport to the Nuclear Medicine Department.…”
Section: Discussionsupporting
confidence: 76%
“…Although similar results were previously described [9], others studies showed LV systolic dysfunction in 22 to 38% acute phase SAH patients [6,40]. This fact probably resulted from our exclusion criteria of patients with a major hemodynamic instability preventing intrahospital transport to the Nuclear Medicine Department.…”
Section: Discussionsupporting
confidence: 76%
“…However, in another study, throughout the 7 days after SAH, lower than normal aldosterone concentrations and normal plasma concentrations of ANP and C-type natriuretic peptides (CNP) were found [26]. B-type natriuretic peptide showed significant diagnostic efficiency for predicting delayed cerebral ischemia after SAH [27]. Rapid natriuresis occurs prior to the development of ischemic symptoms after SAH, indicating that it is a trigger for symptomatic vasospasm [28].…”
Section: Possible Mechanisms Of Nonneurologic Complications Followmentioning
confidence: 99%
“…Systolic dysfunction can be observed by echocardiography as a reduced LV ejection fraction and/or the presence of regional wall motion abnormalities of the LV. LV ejection fraction and pulse-wave velocity were related to poor outcomes following SAH [27]. A multicenter prospective cohort study found that the cardiac index was significantly lower in patients with high grade SAH (World Federation of Neurological Surgeons grades IV and V) on days 1 and 2 after the ictus [76].…”
Section: Manifestations Of Nonneurologic Complications After Sahmentioning
confidence: 99%
“…Several mechanisms for the cardiac complications that occur after SAH have been suggested. A generally accepted hypothesis is that the sympathetic stimulation induces catecholamine release in the myocardium leading to impaired systolic and diastolic function, repolarization abnormalities, and direct myocardial damage [3,7,8]. In addition, it has been reported that during the acute phase of SAH, there is an increase in aortic wall stiffness leading to higher left ventricular pressures [8].…”
Section: Discussionmentioning
confidence: 99%